ANALISIS FAKTOR PENGARUH KESULITAN BELAJAR MATEMATIKA TOPIK PENGELOMPOKAN DATA PADA SISWA KELAS I SD NEGERI GEMAH - Lestari, Putri Ayu; Nuvitalia, Duwi; Purwani, Nur Setya; Wijayanti, Arfilia (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
Learning difficulties are conditions or problems experienced by students, which can reduce academic performance or student learning achievement. This study uses Qualitative Descriptive research conducted at Gemah State Elementary School, Semarang City. The purpose of this study is to describe the factors influencing students' learning difficulties on the grouping of mathematics subject data in grade I of elementary school. The data obtained are in the form of facts in the field. The subjects in this study were class teachers and students in grade 1. This study used written test data collection techniques, interviews, and documentation. The results of this study indicate that students who get scores above the KKM are 17 students or 57%, while students who get scores below the KKM are 13 students or 17% of the total number of students. Based on the results of the discussion, it can be concluded that the influence of learning difficulties in mathematics on the topic of data grouping in grade 1 students of Gemah State Elementary School is influenced by internal factors (motivation, interest, attitude, reading, writing and arithmetic abilities) and external factors (home and school environment).